Comparison of Growth Inhibition of Clostridium perfringens, Clostridium botulinum, and Bacillus cereus During Extended Cooling of Uncured Poultry - Brandon J. Wanless; Jeff Sindelar; Kathleen Ann Glass; Max C Golden (Meat and Muscle Biology)
The 2021 FSIS Appendix B guidelines restrict cooling of meat and poultry products to limit the growth of Clostridium perfringens to no greater than 1-log. This study compared the effect of pH and salt on the growth of 3 sporeforming pathogens, Clostridium perfringens, Bacillus cereus, and Clostridium botulinum during extended cooling in an uncured poultry product. Nine turkey treatments (75% moisture) were formulated using a full factorial design (pH 5.8, 6.2, 6.6; salt 1.2%, 1.5%, 1.8%). Treatments were inoculated with 3-log spores/g of C. perfringens, B. cereus, or C. botulinum and vacuum-packaged (25 g/package). Samples were cooked to 73°C, then cooled from 48.9 °C to 26.7 °C (phase 1) in 1, 1.5, 2, 2.5, or 3 h, from 26.7 °C to 12.8°C (phase 2) and from 12.8°C to 4.4°C (phase 3) in 5 h each. Samples were assayed by enumerating on selective agars at 0-time (post cook before incubation) and at internal temperatures 48.9, 26.7, and 4.4 C. C. botulinum grew < 1-log, and no botulinum toxin was detected regardless of cooling rate or formulation tested. B. cereus was inhibited in all formulations through the 12.5 h total cool (2.5-h phase 1 cooling), but > 1-log increase was observed in pH 6.6 formulations for 13-h total cool. Less than a 1-log C. perfringens growth was detected for all treatments when phase 1 cooling was limited to 1 h, with 1.5-h phase 1 cool for pH < 6.2 with > 1.2% salt, pH 6.6 with > 1.5% salt, and 2-h phase 1 cool for pH < 5.8 and 1.8% salt. All formulations supported a 1- to 3-log increase of C. perfringens when phase 1 cool was 3 h. This study confirms cooling conditions that inhibit C. perfringens will likewise inhibit C. botulinum and B. cereus for the duration of the cooling, and phase 1 cooling can be extended up to 2.5 h depending on salt/pH combinations.